Isolated paroxysmal dysarthria caused by a single demyelinating midbrain lesion. (16th October 2013) - Codeluppi, Luca; Bigliardi, Guido; Chiari, Annalisa; Meletti, Stefano
Abstract : Paroxysmal dysarthria is an unusual condition characterised by brief episodes of dysarthria with the sudden onset and frequent recurrence. It has been mainly reported in multiple sclerosis and an association with midbrain lesions has been claimed; however, most of the reported patients had multiple brain alterations so it was difficult to associate this symptom with a specific lesion site. We illustrate the cases of two patients with an isolated demyelinating midbrain lesion presenting paroxysmal dysarthria as the only symptom; both participants had oligoclonal bands in the cerebrospinal fluid and an unremarkable follow-up. Both patients had benefit from carbamazepine treatment, similarly to previously reported cases. Our report confirms that a demyelinating midbrain lesion is sufficient to provoke paroxysmal dysarthria. It is noteworthy that an erroneous diagnosis of psychogenic disorders was initially made in both cases, highlighting the importance not to underestimate isolated paroxysmal symptoms in clinical practice.